Possibilities of the influence of substitutions of words on the literary language (Eurasian Journal of Philology Science and Education, 2021)
Words and expressions from other languages are divided into different groups according to both function and degree of development. While some acquisitions have only a nominative function, some acquisitions also have an expressive function. The extent to which a language is mastered, limited or widely used, affects the function of derived words. It is clear from observations that purchases made in a limited range are more necessary in creating a stylistic tone than other purchases. The tendency of lexical renewal in the modern Azerbaijani press as a result oh the creation of terms, and this tendency includes the process of replacing many common words of Arabic-Persian origin with Turkisms. The process of mutual enrichment is in many respects accompanied by the influence of the Azerbaijani language on modern Turkish. Under the influence of the Azerbaijani language, Azerbaijani words phrases and sentences are used in the Turkish media especially in Turkish radio and television. It is important to determine the origin of the words and the language to which they belong, In order to reveal the possibilities of the derived words to influence the literary language. Observations show that it is incorrect to consider new words of Turkish origin used in our language until the end of the 19th century, as well as a new words of Turkish origin, which were among the archaisms and re-entered our language. The main thing to pay attention to in this issue is that many new words of Turkish origin have recently passed into our language through Turkish. Most of the new words derived from Turkish are used in parallel with their equivalents in our language and have the function of synonymy.